THE INFLUENTIAL FACTORS OF WORK PRODUCTIVITY DURING COVID-19: THE EFFECT OF DIGITAL SKILL, COLLABORATION, AND ORGANIZATIONAL SUPPORT - Hayat; Bahri; Nopriadi Saputra; Hesty Aisyah; Dyah Palupiningtyas; Farid Ardiansyah; Okta Karneli; Khanifatul Khusna (Fakultas Seni Rupa dan Desain ITB, 2022)
For controlling the negative impact of Covid-19 outbreak, the Indonesia government instructs the citizen to work from home (WFH). Unfortunately, the WFH productivity is still questioned. This study is an attempt to elaborate work productivity and the effect of digital skill as individual driver, digital collaboration as group driver, and perceived organizational support or POS as organizational driver. For supporting the arguments, this article has conducted a quantitative study which involved 824 working citizens as the respondents from all over Indonesia. The respondents are mostly the first timers of working from home. They were working for governmental institution or business organizations from various industries in Indonesia. Collected data was structured and calculated by PLS structural equation modelling) and SmartPLS application version 3. This study concludes that digital skill and POS affect directly on work productivity, but digital collaboration impacts indirectly. Digital skill becomes a mediator in linkage between digital collaboration and work productivity